Hubungan Faktor Sosiodemografi terhadap Kepuasan Pengguna Aplikasi CERDIK (Cerdas Swamedikasi) di Martapura Kalimantan Selatan - Astuti, Karunita; Ramadhani, Syahrizal; Arrahimi, Ahmad Rusadi; Wati, Helmina; Haiqal, Ade (Universitas Borneo Lestari, 2025)
Self-medication is a condition where patients buy drugs without doctor's prescription for common complaints such as fever, pain, dizziness, cough, influenza, ulcers, diarrhea and several skin diseases. Advances in digital technology have influenced various aspects of life including medical services, one of which is the CERDIK application. This study aims to determine respondent satisfaction in using the application and relationship with sociodemographics of the respondents. The method used is non-experimental descriptive on questionnaire in 84 respondents. The results show a very high level of satisfaction with this application. The respondents showed 83 sample (99%) felt very satisfied and only one sample felt quite satisfied with the CERDIK application. The average value of respondent satisfaction overall reached 95%. Furthermore, there is a relationship between sociodemographics including gender, ages, educations and professions with satisfaction using the CERDIK. This shows the application is very helpful for patients in obtaining information about self-medication drugs